Look where you have to go! A field study comparing looking behaviour at urban intersections using a navigation system or a printed route instruction. (October 2015) - Haupt, Juliane; van Nes, Nicole; Risser, Ralf
Highlights: The influence of navigation support on drivers' glance behaviour was analysed. There is an influence on the number and duration of glances at the side road scene. There is an influence on the intersection crossing speed. Using navigation support influences drivers' motive for scanning the side road scene. Abstract: In this study, experienced navigation system users ( N  = 20) drove a given unfamiliar route twice: once with the navigation system activated and once with a printed instruction including a route instruction. Quantitative analysis indicated that drivers passed intersections slower when they used the printed instruction than when they used the navigation system. Drivers looked more often and in proportion longer to the side scene when they used the printed instruction and made less and proportionally shorter glances away from the road scene and to the instruction than when they were supported by the navigation system. No difference was found between these two conditions in the total number of glances and the amount and duration of glances to the forward scene. A qualitative analysis provided understanding of the quantitative results: the type of route guidance was identified to influence drivers' motive for scanning the side road scene. When the navigation system was used the motive was primarily to look for potential hazards and when the printed instruction was used the motive was more focused to look for salient orientation points. The outcomes of the study are discussed in terms of looking motive and the 'look but failed to see' phenomenon.